Isolation, characterisation and cytotoxic effects of antibacterial and antioxidant compounds from selected medicinal plants - Kudumela, Refilwe Given (My University, 2017)
This study was aimed at isolating and evaluating the antibacterial, antioxidant and cytotoxic effects of active compounds from selected medicinal plant species. The biological activities and cytotoxic effects of Commelina africana, Dombeya rotundifolia, Elephantorrhiza elephantina and Schkuhria pinnata were investigated based on their traditional uses. The plants were extracted with different solvents of varying polarities. Methanol was the best extractant with the highest yield. The presence of different phytoconstituents was screened using standard methods; this revealed the presence of terpenoids, flavonoids, tannins, and saponins. Meanwhile, the phytochemicals were screened on TLC, where different colours observed indicated the presence of different compounds. The total phenolic, tannin and flavonoid content were estimated using spectrophotometric methods. D. rotundifolia had the highest amounts of phenol, tannin and flavonoid content, while S. pinnata had the least. The antibacterial and antioxidant screening employed both qualitative and quantitative assays. Although not separated, this study demonstrated the antioxidant potential of D. rotundifolia extracts developed in BEA and CEF. D. rotundifolia also demonstrated the highest free radical scavenging and reducing power antioxidant potential. These activities could be attributed to the high phenolic, tannin and flavonoid content observed. All the selected plants had antibacterial potential against E. coli and P. aeruginosa. Only S. pinnata extracts were active against E. faecalis and S. aureus. The MIC values of the plants and ampicillin ranged from 0.02 to 2.50 mg/mL and 0.02 to 0.08 mg/mL, respectively. The plants were combined to determine any interaction effects in exhibiting antibacterial activity. Among all the possible combinations, combinations with S. pinnata had improved antibacterial activity. The effects of D. rotundifolia and S. pinnata extracts on the inhibition of the production of reactive oxygen species on LPS-induced RAW 264.7 macrophages was determined using the DCFHD-A assay. Both plants demonstrated anti-inflammatory potential by inhibiting the production of ROS in a dose-dependent manner. Cell viability assays revealed that S. pinnata had cytotoxic effects on African green monkey kidney (Vero) cells with the lowest LC50 (25 µg/mL). Bioassay guided fractionation and nuclear magnetic resonance spectroscopy of dichloromethane extracts of S. pinnata on column chromatography afforded isolation and characterisation of three sesquiterpene lactones. These were identified as 6-(2, 3- xxvi dihydroangeloylory)-6α-hydroxyinuviscolide, heliangolide and eucannabiolide. All three compounds had antibacterial, anti-inflammatory and cytotoxic effects. The compounds may serve as leads for synthesis of less toxic therapeutic antibacterial and anti-inflammatory drugs in the pharmaceutical industry.
Thesis (MSc. (Microbiology)) -- University of Limpopo, 2017
Keywords: Medicinal plant species; Antibacterial effects; Antioxidant effects; Cytotoxic effects; Medicinal plants; Fosfomycin; Antibacterial agents; Antioxidants; Antineoplastic antibiotics